The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1093/nar/gkp234
|View full text |Cite
|
Sign up to set email alerts
|

Local and global effects of strong DNA bending induced during molecular dynamics simulations

Abstract: DNA bending plays an important role in many biological processes, but its molecular and energetic details as a function of base sequence remain to be fully understood. Using a recently developed restraint, we have studied the controlled bending of four different B-DNA oligomers using molecular dynamics simulations. Umbrella sampling with the AMBER program and the recent parmbsc0 force field yield free energy curves for bending. Bending 15-base pair oligomers by 90° requires roughly 5 kcal mol−1, while reaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
95
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 50 publications
14
95
0
Order By: Relevance
“…Importantly, the nick-dependent flexible defect excitation has a sensitive dependence on temperature, which is significantly suppressed when the temperature is reduced from 300 K to 290 K [46]. These and previous simulations performed for sharply bent, nick-free DNA also revealed that excitation of flexible defects involves basepair disruptions [45,46,53], which result in local kinks around the defects. However, excitation of flexible defects inside nick-free DNA is much less favorable than those at nicked sites.…”
Section: Nick-dependent Defect Excitation In Sharply Bent Dnasupporting
confidence: 62%
See 1 more Smart Citation
“…Importantly, the nick-dependent flexible defect excitation has a sensitive dependence on temperature, which is significantly suppressed when the temperature is reduced from 300 K to 290 K [46]. These and previous simulations performed for sharply bent, nick-free DNA also revealed that excitation of flexible defects involves basepair disruptions [45,46,53], which result in local kinks around the defects. However, excitation of flexible defects inside nick-free DNA is much less favorable than those at nicked sites.…”
Section: Nick-dependent Defect Excitation In Sharply Bent Dnasupporting
confidence: 62%
“…Among these possible defects, both a locally melted DNA basepairs [45,46] and an intrinsically kinked DNA basepair step [45,47] have been observed in molecular dynamics (MD) simulations of sharply bent DNA molecules.…”
Section: Excitation Of Flexible Defectsmentioning
confidence: 99%
“…Further, it has much heavier than small molecules. Recent study 33 of 15-base pair oligomer of single stranded nucleic acid fragments showed that the bending by 90º requires roughly 5 kcal mol -1 where the effective bending force constants of 0.02 ~ 0.06 kcal mol -1 degree -2 was reported. This corresponds to roughly 0.46 ~ 1.4 mdynÅ which is yet very huge in fact.…”
mentioning
confidence: 99%
“…The importance of kinks for strong DNA bending was predicted by Crick and Klug [90], and kinks or internal bubbles due to local DNA melting (that is, the loss of base pairing) will increase the cyclization rate [91,92]. Type II kinks were observed in free energy simulations that used a global screw-axis coordinate to bend DNA [93]. A change in the free energy cost of bending from the quadratic to the linear regime was observed at high bending angles, where type II kinks were prevalent.…”
Section: Bending Of Bare Dnamentioning
confidence: 99%